Frankenweenie [videorecording (DVD)] - Burton, Tim, 1958-; Ryder, Winona, 1971-; Short, Martin, 1950-; O'Hara, Catherine (Disney DVD., 2012)
Young Victor conducts a science experiment that will bring his dog Sparky back to life, only to face unintended, sometimes monstrous consequences.